2018
DOI: 10.1002/hed.25315
|View full text |Cite
|
Sign up to set email alerts
|

Nasal fibroscopy as a routine screening procedure of sinonasal adenocarcinoma of woodworkers: French longitudinal case study

Abstract: Flexible nasoendoscopy offers meaningful efficacy and a promising safety profile, and, therefore, could become the new cornerstone of the routine screening procedure of sinonasal adenocarcinoma among woodworkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Univariate analysis demonstrated that all variables, except race/ethnicity and sex, were significantly associated with HPV testing. The HPV testing rates varied the most by age (65% for those <50 years vs 41% 751 years), diagnosis year (29% in 2010 vs 75% in 2014), and site (60% oropharynx vs 24% soft palate). The following variables were significantly associated with HPV testing in the logistic model (P < .05): later diagnosis year, cancer of the oropharynx, poorly differentiated grade (vs well differentiated), receiving surgery, and being treated at a hospital with 5001 beds.…”
Section: Res U Ltsmentioning
confidence: 99%
“…Univariate analysis demonstrated that all variables, except race/ethnicity and sex, were significantly associated with HPV testing. The HPV testing rates varied the most by age (65% for those <50 years vs 41% 751 years), diagnosis year (29% in 2010 vs 75% in 2014), and site (60% oropharynx vs 24% soft palate). The following variables were significantly associated with HPV testing in the logistic model (P < .05): later diagnosis year, cancer of the oropharynx, poorly differentiated grade (vs well differentiated), receiving surgery, and being treated at a hospital with 5001 beds.…”
Section: Res U Ltsmentioning
confidence: 99%
“…Flexible endoscopy is a routine practice of otolaryngology for viewing nasal cavity, nasopharynx and larynx while is rarely used in paranasal sinus. Although some literature reported the usage of flexible endoscope in sinus lesions, more specific research data are needed [9,[14][15][16].…”
mentioning
confidence: 99%